Bookstagram Community’s Book Review: A Reciprocal Ethnography Study - I Gede Satwika Bayu Darma; Sherina Friskila Nurtiara; Rebecca Amanda; Rosi Nindyana; Moh. Naufal Rifki Meisandy (JELLE : Journal Of English Literature, Linguistics, and Education, 2021)
This article aims to deliver the results of our study on one of bookstagram community’s activities, namely book review. The study focuses on how the activity serves as a tradition that shapes the community’s identity. Employing reciprocal ethnography approach, we found that the book review activity (which is done repeatedly and continuously) is a form of invented tradition that confirms the community’s motive to influence readers to read and understand the reviewed books in various perspectives, in addition to getting in touch and creating bonds with other book readers. The review is a process carried out by bookstagrammers (nickname for bookstagram community’s members) to deliver their understanding about certain books in different point of views. In addition, discussion and talks on Instagram elicited by the bookstagrammers’ reviews in the form of comments show that this tradition has significantly become a part of the community’s identity. Keywords: Bookstagram Community, book review, reciprocal ethnography